2020
DOI: 10.3389/fphys.2020.584135
|View full text |Cite
|
Sign up to set email alerts
|

Vasculo-Neuronal Coupling and Neurovascular Coupling at the Neurovascular Unit: Impact of Hypertension

Abstract: Components of the neurovascular unit (NVU) establish dynamic crosstalk that regulates cerebral blood flow and maintain brain homeostasis. Here, we describe accumulating evidence for cellular elements of the NVU contributing to critical physiological processes such as cerebral autoregulation, neurovascular coupling, and vasculoneuronal coupling. We discuss how alterations in the cellular mechanisms governing NVU homeostasis can lead to pathological changes in which vascular endothelial and smooth muscle cell, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 235 publications
1
51
0
Order By: Relevance
“…Although many of the above treatments have proved effective in animal stroke models, none have proved effective in treating stroke patients in clinical trials until now, 34 perhaps due to differences between animal models and humans. Meanwhile, stroke patients often have comorbid disease, such as hypertension, diabetes, hyperlipemia, and even aging, 2,14,35,36 which might impact the effectiveness of the therapy. Accurate animal models that better match with the stroke population should be established and the role of NVU in stroke requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many of the above treatments have proved effective in animal stroke models, none have proved effective in treating stroke patients in clinical trials until now, 34 perhaps due to differences between animal models and humans. Meanwhile, stroke patients often have comorbid disease, such as hypertension, diabetes, hyperlipemia, and even aging, 2,14,35,36 which might impact the effectiveness of the therapy. Accurate animal models that better match with the stroke population should be established and the role of NVU in stroke requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of the NVU, which is comprised of neurons, astrocytes, pericytes, microglia, endothelial cells, and vascular smooth muscle cells (VSMCs), was formalized at the 2001 Stroke Progress Review Group meeting of the National Institute of Neurological Disorders and Stroke (https://www.ninds.nih.gov/About-NINDS/Strategic-Plans-Evaluations/Strategic-Plans/Stroke-Progress-Review-Group) and demonstrated that components of the NVU in the central nervous system communicated dynamically with each other and maintained hemostasis of the brain 13 . The interaction and signaling between different components of the NVU are very complicated, and latest advances have shown that the NVU might regulate cerebral blood flow and maintain brain homeostasis through neurovascular coupling or vasculoneuronal coupling 13–15 . Meanwhile, it was recently suggested that astrocytes or microglia, which have multiple phenotypes, have controversial effects on the regulation of neuroinflammation or neurovascular coupling and require further investigation 16–19 .…”
Section: Introductionmentioning
confidence: 99%
“…However, considering that neurovascular coupling is largely reported as a percent change in CBF from baseline, understanding the cellular mechanisms governing baseline tone is critical as these processes could impact the waveform (e.g., onset, amplitude, duration) of the neurovascular coupling response. Here, we used an experimental paradigm that not only evaluates the cellular mechanisms underlying baseline tone but also the flow of information at the NVU under circumstances in which the signal (or stimulus) is of vascular origin, such as intravascular pressure and/or flow, a phenomenon termed vasculo-neuronal coupling (VNC) [ 11 , 68 ]. A major finding of this study is that BCAS mice showed reduced parenchymal arteriole constriction-induced inhibition of pyramidal neuron firing activity.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that the infusion of asymmetric dimethylarginine, an endogenous inhibitor of NO, reduced vascular function, increased arterial stiffness, and decreased cerebral blood flow in healthy subjects [32]. In addition, endothelial mediated vasodilation is caused by electrical coupling between the endothelium and vascular smooth muscle interaction that drive hyperpolarization by adenosine and potassium ion (K + ) [33]. Adenosine activates adenyl cyclase and protein kinase A, stimulating K + channels in the endothelium and vascular smooth muscle, resulting in vasodilation.…”
Section: Discussionmentioning
confidence: 99%